Associations between the Mixture of Governance Modes and the Performance of Local Public Service Delivery - Swe, Yin Lei Win (2019)
Since the Myanmar central government decentralized some of its power to state and regional governments, few studies investigated the performance of local governments, and no studies investigated the relationships between the types of governance modes and the performance of public service delivery. This study investigates the associations between three types of governance—i.e., hierarchy, market, and network—and the multiple performances of agricultural services in terms of the competing public values of efficiency, effectiveness and equity in southern Shan State. The findings indicate that the three types of governance simultaneously coexist in local agriculture departments and that their associations with the performances of public services differ. Network governance is negatively associated with efficiency, effectiveness, and equity during its initial stage, but these associations become positive when the degree of network governance increases in agriculture departments. In contrast, market governance is positively related to effectiveness and equity during its initial stage; however, increasing the degree of market governance further leads to a negative association with both public service values. This assessment of the performance of public programmes in terms of the trade-offs among public service values contributes to improving the local governance of public service delivery not only in Myanmar but also in other developing countries.